Pre-Service Teachers and Participatory Action Research: Students, Community, and Action - Paul Mencke (Networks: An Online Journal for Teacher Research, 2013)
Participatory Action Research (PAR) has a history of empowerment, transformation, and healing (McIntyre, 2008). Its limited use in teacher education must be addressed, and this study shows pre-service teachers’ overwhelming enjoyment in completing a PAR project. An outline of classroom methods demonstrates how the project was implemented, and 41 student responses are analyzed from a secondary Community and Cultural Context of Education course. Findings indicate 73% concluded PAR was great or enjoyable, and included are reflections about transformational experiences, reasons for not enjoying PAR, and ideas to improve the project. Implications for continued study suggest a need for further inquiry through interviews, pre-service teachers’ likelihood of using PAR in future classrooms, and PAR in method or content courses.